# How to Multiply Binomials

## Multiply Binomials When Coefficient is One - How it Works - Video

### Example 1 Example 1:

When we distribute two binomials, one method is use the FOIL method. F is for the first terms in each parenthesis. O is for the second terms in each parenthesis. I is for the second term in the first parenthesis and the first term in the second parenthesis. L is for the second term in the first parenthesis and the second term in the second parenthesis.

For F we multiply the x and x => x2.

For O we multiply the x and 4 => 4x.

For I we multiply the 6 and x => 6x.

For L we multiply the 6 and 4 => 24.

Now we have x2 + 4x + 6x + 24. Let's combine any like times and in this case we have 4x + 6x => 10x.

So our final answer is x2 + 10x + 24.

### Example 2 Example 2:

When we distribute two binomials, one method is use the FOIL method. F is for the first terms in each parenthesis. O is for the second terms in each parenthesis. I is for the second term in the first parenthesis and the first term in the second parenthesis. L is for the second term in the first parenthesis and the second term in the second parenthesis.

For F we multiply the x and x => x2.

For O we multiply the x and 5 => 5x.

For I we multiply the -3 and x => -3x.

For L we multiply the -3 and 5 => -15.

Now we have x2 + 5x - 3x - 14. Let's combine any like times and in this case we have 5x - 3x => 2x.

So our final answer is x2 + 2x - 15.

### Example 3 Example 3:

When we distribute two binomials, one method is use the FOIL method. F is for the first terms in each parenthesis. O is for the second terms in each parenthesis. I is for the second term in the first parenthesis and the first term in the second parenthesis. L is for the second term in the first parenthesis and the second term in the second parenthesis.

For F we multiply the x and x => x2.

For O we multiply the x and -4 => -4x.

For I we multiply the 2 and x => 2x.

For L we multiply the 2 and -4 => -8.

Now we have x2 - 4x + 2x - 8. Let's combine any like times and in this case we have -4x + 2x => -2x.

So our final answer is x2 - 2x - 8.

### Example 4 Example 4:

When we distribute two binomials, one method is use the FOIL method. F is for the first terms in each parenthesis. O is for the second terms in each parenthesis. I is for the second term in the first parenthesis and the first term in the second parenthesis. L is for the second term in the first parenthesis and the second term in the second parenthesis.

For F we multiply the x and x => x2.

For O we multiply the x and -7 => -7x.

For I we multiply the -2 and x => -2x.

For L we multiply the -2 and -7 => -14.

Now we have x2 - 7x - 2x - 14. Let's combine any like times and in this case we have -7x - 2x => -9x.

So our final answer is x2 - 9x - 14.